2020
DOI: 10.3390/ijms21134777
|View full text |Cite
|
Sign up to set email alerts
|

NRF2, a Transcription Factor for Stress Response and Beyond

Abstract: Nuclear factor erythroid 2-related factor 2 (NRF2) is a transcription factor that regulates the cellular defense against toxic and oxidative insults through the expression of genes involved in oxidative stress response and drug detoxification. NRF2 activation renders cells resistant to chemical carcinogens and inflammatory challenges. In addition to antioxidant responses, NRF2 is involved in many other cellular processes, including metabolism and inflammation, and its functions are beyond the originall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
588
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 984 publications
(602 citation statements)
references
References 150 publications
6
588
0
8
Order By: Relevance
“…NRF2 activation is an important endogenous antioxidant mechanism protecting against oxidative stress [ 22 , 24 , 81 , 82 ]. It has been shown that under hypoxia-ischemia conditions, the expression of NRF2 is enhanced, released from Keap1, and translocated to the nucleus, binding to the ARE sequences.…”
Section: Discussionmentioning
confidence: 99%
“…NRF2 activation is an important endogenous antioxidant mechanism protecting against oxidative stress [ 22 , 24 , 81 , 82 ]. It has been shown that under hypoxia-ischemia conditions, the expression of NRF2 is enhanced, released from Keap1, and translocated to the nucleus, binding to the ARE sequences.…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with MAFLD, Nrf2 activation occurs in response to disease development, but the expression of antioxidant enzymes seems to decrease as MAFLD progresses [ 39 ]. Nrf2-knockout (Nrf2-KO) cells have lower levels of glutathione, whereas Keap1 deficiency promotes glutathione upregulation [ 24 , 40 ]. The induction of the Keap1/Nrf2 signaling pathway may provide protection to hepatic cells from oxidative stress and avoid the progression of MAFLD [ 41 ].…”
Section: Nrf2 Connection With Liver Diseasesmentioning
confidence: 99%
“…The induction of the Keap1/Nrf2 signaling pathway may provide protection to hepatic cells from oxidative stress and avoid the progression of MAFLD [ 41 ]. A microarray study revealed that both genetic and pharmacologic activation of Nrf2 resulted in induction of pathways beyond detoxification and cytoprotection, including genes of lipid metabolism [ 9 , 40 ]. Nrf2 activation also inhibits the transcription of IL-6 and IL-1β [ 40 ] and reduces hepatic glucose production in humans [ 32 ].…”
Section: Nrf2 Connection With Liver Diseasesmentioning
confidence: 99%
See 2 more Smart Citations